Added value of plasma metabolomics to describe maternal effects in rat maternal and prenatal toxicity studies. (February 2019) - Keller, J.; Mellert, W.; Sperber, S.; Kamp, H.; Jiang, X.; Fabian, E.; Herold, M.; Walk, T.; Strauss, V.; van Ravenzwaay, B.
Highlights: Metabolomics is a useful tool for a mechanism-based identification of rat maternal toxicity. The metabolome-derived NOEL was more sensitive in detecting maternal toxicity than the maternal NOAEL. Specific metabolome patterns were established in pregnant rats. Abstract: For regulatory purposes prenatal developmental toxicity (OECD No. 414) studies are routinely performed in our laboratories. The suitability of metabolomics as technology to identify maternal toxicity in such studies was investigated. Plasma was sampled from pregnant, non-fasted rats on gestation day 20 before cesarean section. Metabolite profiling was performed by gas- and liquid-chromatography-tandem mass spectrometry techniques. The sensitivity of routinely examined maternal toxicity parameters (OECD No. 414) was compared to those of metabolome analysis. Evaluating 44 studies, the metabolome-derived NOEL was more sensitive in 45% of the cases in detecting maternal toxicity than the maternal NOAEL. Metabolome patterns indicative for liver effects and 4-hydroxyphenylpyruvate dioxygenase (HPPD) enzyme-inhibition were established in pregnant rats based on regulated metabolites using reference compounds. The HPPD inhibition and liver toxicity patterns in pregnant rats were reasonably comparable to the ones established in non-pregnant, fasted rats. Metabolomics is a useful tool for an improved and mechanism-based identification of maternal toxicity in maternal and prenatal toxicity studies. The data suggest that the current classical maternal toxicity parameters may underestimate the extent of effects of compounds on the dams.